Covid-19 and the South African Pentecostal Landscape: Historic Shift from Offline Liturgical Practice to Online Platforms - John Mhandu and Vivian Ojong (Journal for the Study of Religion)
The Coronavirus (Covid-19) disease resulted in an epic shift from offline liturgical practice to online platforms where South African Pentecostal churches are worshiping, using online tools such as Zoom. This article explores how offline liturgical practices, traditional power dynamics, and the performative and communication characteristics of Pentecostalism are decoded into the digital space, and the impact it has on congregants and church leadership. The self-image of South African Pentecostalism is un-packed in the context of Covid-19. Grounded in the interpretivist research paradigm, the article draws on telephonic interviews conducted with 20 purposively selected Pentecostal lay leaders and pastors in the eThekwini district, KwaZulu-Natal. The article uses the Giddens theory of structuration to understand the social structural challenges emanating from an online liturgical practice. The prohibition of gatherings to promote social distancing culminated in the use of online platforms as an alternative to physical gatherings. Key findings suggest that this historic shift created a plethora of challenges for Pentecostal churches in Durban, resulting in some being unable to reopen. Moving to online platforms meant that South African Pentecostal churches in Durban had to adapt to new modalities of practice in transmitting sacred information. By depriving Pentecostal churches the opportunity to perform rituals of solidarity and other offline liturgical practices, Covid-19 disrupted important social systems and its performative and communication traits. Despite the challenges and changes caused by this novel pandemic, this study also found that Covid-19 provided an opportunity to assess the doctrines of Pentecostal leaders. In other words, online worship is coupled with benefits that must not be overlooked.